Measuring and Predicting Heterogeneous Recessions - Cem Çakmaklı; Richard Paap; Dick van Dijk (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper conducts an empirical analysis of the heterogeneity of recessions in monthly U.S. coincident and leading indicator variables. Univariate Markovswitching models indicate that it is appropriate to allow for two distinct recession regimes, corresponding with 'mild' and 'severe' recessions. All downturns start with a mild decline in the level of economic activity. Contractions that develop into severe recessions mostly correspond with periods of substantial credit squeezes as suggested by the 'financial accelerator' theory. Multivariate Markov-switching models that allow for phase shifts between the cyclical regimes of industrial production and the Conference Board Leading Economic Index confirm these findings.
Keywords: C11; C32; C51; C52; E32; 330; Business cycle; phase shifts; regime-switching models; Bayesian analysis; Konjunktur; Markov-Kette; Bayes-Statistik; Schätzung; USA